Application of Palm Stearin Edible Coating on Cavendish Banana (Musa acuminata). Issue 1 (1st June 2022) - Agusta, W; Anggraeni, D; Hermansyah, H D; Gebrina, A D
Abstract: Palm stearin has the potential to alter the use of beeswax. This study aimed to assess the effect of palm stearin as an edible coating on the quality changes of Cavendish banana during storage. The samples of Cavendish banana were stored within eight days with treatment combinations of temperature (room temperature: 28 °C and 10 °C) and application of edible coating (control: without coating, and coated with palm stearin). During the storage period, physicochemical properties of the samples were evaluated in terms of weight loss, fruit firmness, total soluble solids, ascorbic acid content, respiration rate, and peel colour. The obtained results showed that storage temperature and storing period significantly (p< 0.05) affected the properties of Cavendish banana in terms of weight loss, fruit firmness, CO2 evolution, and O2 consumption. Application of palm stearin edible coating significantly affected (p< 0.05) weight loss and ascorbic acid content. Palm stearin edible coating at room temperature reduced weight loss and maintained ascorbic acid content. On the eighth day of storage, coated samples and controls stored at room temperature lose their weight up to 12.96 % and 23.94 % on average, respectively.